2014
DOI: 10.2135/cropsci2014.05.0393
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Soybean Aphid Resistance in Soybean Across Different Temperatures

Abstract: The soybean aphid (Aphis glycines Matsumura) is the most important insect pest posing a threat to soybean [Glycine max (L.) Merr.] grain production in the United States. Soybean cultivars with resistance are currently being deployed to aid in management of the pest. Temperature has been reported to influence the expression of host plant resistance against crop pests. The objective of this study was to determine if temperatures, 14, 21, and 28°C, altered resistance expression in four aphid‐resistant soybean gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…However, without a susceptible line as a control, the results are inconclusive. Furthermore, other studies with the soybean aphid (Richardson 2011, Chirumamilla et al 2014 found a decrease, rather than increase, in the expression of resistance at low temperature. The conflicting findings underscore the need for additional research on this crop-pest system using consistent experimental methods and a broad range of temperatures (see Recommendations for Future Research).…”
Section: Enhanced Resistance At High and Low Temperaturesmentioning
confidence: 85%
See 3 more Smart Citations
“…However, without a susceptible line as a control, the results are inconclusive. Furthermore, other studies with the soybean aphid (Richardson 2011, Chirumamilla et al 2014 found a decrease, rather than increase, in the expression of resistance at low temperature. The conflicting findings underscore the need for additional research on this crop-pest system using consistent experimental methods and a broad range of temperatures (see Recommendations for Future Research).…”
Section: Enhanced Resistance At High and Low Temperaturesmentioning
confidence: 85%
“…Experiments with biotypes of the soybean aphid on resistant and susceptible soybean lines provide additional evidence that low temperatures suppress plant resistance. Richardson (2011) and Chirumamilla et al (2014) showed that differences in aphid numbers between resistant and susceptible soybeans were smaller at the lowest temperature tested (14°C) compared to higher temperatures (21 and 28°C). In addition, Hough et al (2017) reported a smaller difference in the intrinsic population growth rate of the soybean aphid between resistant and susceptible soybeans at 15°C compared to higher temperatures (20-30°C).…”
Section: Reduced Resistance At Low Temperaturesmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, there may be interactions between abiotic factors, like temperature, on the impact of Rag genes [ 37 , 38 ]. However, the extent that the protection from all Rag genes is influenced by temperature is unknown [ 39 ]. Given these sources of variation in methodology, it is difficult to compare across studies.…”
Section: Discussionmentioning
confidence: 99%